Correction to: Comprehensive 5P framework for active aging using the ecological approach: an iterative systematic review - Azadeh Lak; Parichehr Rashidghalam; Phyo K. Myint; Hamid R. Baradaran (BMC, 2020)
It was highlighted that the original article [1] contained a spelling mistake in the name of Hamid R. Baradaran. This was incorrectly captured as Bradaran. The original article has been updated.